Impact of Aging on Liver Histological Findings of Autoimmune Liver Diseases - Yuki Haga (Diseases, 2014)
Our aim is to investigate the recent liver biopsy findings of autoimmune liver diseases at a university hospital located in an urban area of Japan. The study included 259 patients (mean age 56.8 ± 12.5; male/female, 46/213) who underwent a liver biopsy for primary biliary cirrhosis (PBC) or autoimmune hepatitis (AIH). We analyzed their liver biopsy findings according to age and gender. Among 127 PBC patients, Scheuer stages 1, 2, 3, and 4 were 42, 54, 18, and 13, respectively. Among 101 AIH patients, fibrosis stages F1, F2, F3, and F4 were 37, 32, 19, and 13, respectively, and inflammatory activity grades A1, A2, and A3 were 22, 25, and 54, respectively. Among PBC aged ≥65 years, Scheuer stages 1–3 and 4 patients were 27 and 6, respectively. The proportion of Scheuer stage 4 patients in PBC aged ≥65 years tended to be higher than that in PBC aged <65 years (p = 0.0659). Of interest, the proportion of AIH patients with moderate or severe activity (A2 or A3) in males was higher than in females (p = 0.0311). From the point of view of fibrosis stage or inflammatory activity grade of the liver, the proportion of AIH patients aged ≥65 years was similar to that aged <65 years. Although we identified six older cirrhotic patients with AIH, three of them were male. The progression of fibrosis and inflammatory activity of the liver should be noted when we treat older patients suffering from autoimmune liver diseases. Liver biopsy plays an important role in obtaining accurate information on autoimmune liver diseases in older patients.